1956
DOI: 10.1128/jb.72.2.209-213.1956
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF CARBON DIOXIDE ON POLYSACCHARIDE PRODUCTION BY STREPTOCOCCUS BOVIS

Abstract: Polysaccharide production by streptococci from sucrose or raffinose has generally been examined by one of two methods-streak or pour plates containing carbohydrate and incubated under air or broth cultures containing the carbohydrate. In the former method polysaccharide production is accompanied by the development of large, confluent moist colonies, usually slimy in appearance. With the latter method, polysaccharide formation is accompanied by an increased viscosity of the broth, sometimes to the point of soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1957
1957
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In these organisms, however, the enzyme responsible for dextran synthesis does not appear to have been isolated or examined. Recently it was shown that various strains of Streptococcus bovis produce dextran in sucrose cultures only in the presence of added carbon dioxide (Dain, Neal & Seely, 1956;Bailey & Oxford, 1958a, b). In Leuconostoc species, however, dextran production appears to be independent of added carbon dioxide (Bailey & Oxford, 1958a).…”
mentioning
confidence: 99%
“…In these organisms, however, the enzyme responsible for dextran synthesis does not appear to have been isolated or examined. Recently it was shown that various strains of Streptococcus bovis produce dextran in sucrose cultures only in the presence of added carbon dioxide (Dain, Neal & Seely, 1956;Bailey & Oxford, 1958a, b). In Leuconostoc species, however, dextran production appears to be independent of added carbon dioxide (Bailey & Oxford, 1958a).…”
mentioning
confidence: 99%
“…This difference in adsorption characteristics between E. coliand S. bovis was thought to be related to the relative ability of the organisms to effect cell-to-clay surface bridging by means of the extracellular polymers produced. That E. coli and S. bovis are capable of excreting polysaccharides in culture media has been reported by many workers (Niven and White, 1948;Dain et al, 1956;Sutherlandand Wilkinson, 1964;Knoxand Work, 1966). However, whether or not these organisms can do likewise in soil has not, to our knowledge, been previously shown.…”
Section: Bacteria On Clay Surfaces 195mentioning
confidence: 72%
“…37 No other single factor appears as important as COz in controlling the production of polysaccharides by Strepto-COCCUS bovis. 38 Additionally, it appears that growth and slime or spore formation by microbial species may be stimulated or repressed by C02. 39 Specifically, in mammalian cell cultures, it has been observed that high levels of C 0 2 may inhibit the movement of mitochondria in chick fibrobla~ts,~O yet in its absence chick blastoderm degenerate^,^^ and HeLa, L-929, and primary monkey kidney cell growth appear inhibited.4P It has been reported that complete inhibition of outgrowth of rat kidney, rat fibroblast and Jensen sarcoma explants occurred when the partial pressure of C02 exceeded 400 mm.…”
Section: Oxygenmentioning
confidence: 99%